Complete versus Partial Molar Pregnancies: A Global Systematic Review of Risk Predictors, Radiologic Findings, and Maternal Prognosis - Rasheed, Saadia; Abdulla, Saba; Wasiq, Syeda Noamrah; Shams, Amber; Cheema, Ramesa (Journal of Neonatal Surgery, 2025)
Background: Hydatidiform mole, encompassing complete and partial molar pregnancies, remains a distinctive subset of gestational trophoblastic disease (GTD) with variable clinical and prognostic outcomes. Despite advances in imaging and molecular diagnostics, distinguishing complete from partial forms remains a clinical challenge with significant implications for maternal prognosis. This systematic review aimed to synthesise global evidence on epidemiologic risk predictors, radiologic findings, and maternal outcomes associated with complete versus partial molar pregnancies. Methods: A systematic review of English-language studies published between January 2000 and June 2025 was conducted following PRISMA 2020 guidelines. Searches across PubMed, Scopus, and Embase identified observational, cohort, and meta-analytic studies comparing complete and partial molar pregnancies. Data were extracted on demographic risk predictors, ultrasonographic findings, β-hCG trends, and maternal complications including gestational trophoblastic neoplasia (GTN). Methodological quality was assessed using the Newcastle–Ottawa Scale. Results were qualitatively synthesised with textual tables. Findings: Thirty-eight studies encompassing 14,642 patients were included. Advanced maternal age (>35 years), Asian ethnicity, and a prior molar pregnancy were significant predictors of complete moles. Partial moles were more commonly associated with spontaneous conception in younger women. Ultrasonographically, complete moles exhibited diffuse vesicular patterns (“snowstorm” appearance) and absence of fetal tissue, whereas partial moles showed focal cystic changes or a malformed fetus. The incidence of post-molar GTN was markedly higher after complete moles (15–20%) compared with partial moles (1–5%). Maternal complications including pre-eclampsia, thyrotoxicosis, and haemorrhage occurred predominantly in complete molar pregnancies. Interpretation: Complete molar pregnancies carry substantially greater oncologic and obstetric risks than partial forms. Early differentiation using combined radiologic, biochemical, and genetic assessment is essential for guiding management and follow-up. Integration of molecular genotyping into diagnostic protocols may improve prognostic stratification globally. Funding: No specific funding was received for this study